Electromagnetic Materials : Proceedings of the International Conference on Materials for Advanced Technologies (Symposium P). - Hock, Lim (World Scientific, 2007)
The contributions to this volume deliberate the electrical and magnetic properties of materials relevant to the design of unconventional antennas, microwave circuits/components, anti-reflection media and coatings, EMI shielding structures, radomes, etc. Though a classical research topic, some recent advancements in technology have led to new capabilities to create and control fine-scale structures. This has inspired scientists to develop new materials with exceptionally high permittivity or permeability, as well as metamaterials (or negative index materials) with unusual electromagnetic proper.